Association between cigarette smoking and the risk of major psychiatric disorders: a systematic review and meta-analysis in depression, schizophrenia, and bipolar disorder - Hu, Zhonghou; Cui, Enxiu; Chen, Bo; Zhang, Mi (Frontiers in Medicine, 2025)
BackgroundThe prevalence of cigarette smoking among patients with major psychiatric conditions is significantly higher than that in the general population. However, whether there is a causal association between cigarette smoking and major psychiatric disorders remains unclear. Therefore, we conducted a systematic review and meta-analysis of cohort studies to elucidate the association between cigarette smoking and the risk of major psychiatric disorders, including depression, schizophrenia, and bipolar disorder.MethodsWe systematically searched PubMed, Embase, and the Cochrane Library for potentially eligible studies from their inception until March 2, 2024. All pooled analyses were performed using a random-effects model, and exploratory sensitivity and subgroup analyses were conducted.ResultsTwenty-five cohort studies involving 2,917,030 individuals were included in the meta-analysis. The summary results indicated that both current smoking (relative risk [RR], 1.30; 95% confidence interval [CI], 1.18–1.43; P < 0.001) and former smoking (RR, 1.16; 95% CI, 1.09–1.23; P < 0.001) were associated with an elevated risk of major depression. Additionally, current smoking was significantly associated with an elevated risk of schizophrenia (RR, 1.84; 95% CI, 1.07–3.19; P = 0.028) and bipolar disorder (RR, 1.54; 95% CI, 1.22–1.95; P < 0.001).ConclusionCurrent smoking is significantly associated with an elevated risk of major psychiatric disorders, including major depression, schizophrenia, and bipolar disorder. Former smokers also have an elevated risk of major depression. However, it should be noted that, despite these significant associations, due to the nature of the cohort studies included, this study cannot establish a causal relationship between cigarette smoking and major psychiatric disorders.Systematic review registrationhttps://inplasy.com/inplasy-2024-3-0093/, identifier INPLASY202430093.